Preparation of periodic surface structures on doped poly(methyl metacrylate) films by irradiation with KrF excimer laser - Kalachyova, Yevgeniya; Lyutakov, Oleksiy; Slepicka, Petr; Elashnikov, Roman; Svorcik, Vaclav (Nanoscale research letters, 2014)
In this work, we describe laser modification of poly(methyl methacrylate) films doped with Fast Red ITR, followed by dopant exclusion from the bulk polymer. By this procedure, the polymer can be modified under extremely mild conditions. Creation of surface ordered structure was observed already after application of 15 pulses and 12 mJ cm(-2) fluence. Formation of grating begins in the hottest places and tends to form concentric semi-circles around them. The mechanism of surface ordered structure formation is attributed to polymer ablation, which is more pronounced in the place of higher light intensity. The smoothness of the underlying substrate plays a key role in the quality of surface ordered structure. Most regular grating structures were obtained on polymer films deposited on atomically 'flat' Si substrates. After laser patterning, the dopant was removed from the polymer by soaking the film in methanol.
Keywords: Surface; Grating; Polymer; Laser; Modification